Information Technology Governance Framework in the Public Sector Organizations - Lanto Ningrayati Amali; M. Mahmuddin; Mazida Ahmad (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
This paper discusses the framework of IT (Information Technology) governance in the public sector organizations and the factors that contribute to the implementation of IT governance in the province of Gorontalo, Indonesia. The problem that occurs is the absence of such a framework which can provide the basis, functions and limits for the efficient use of IT resources, IT strategic alignment and the management of risk in public organizations. Descriptive approach used to identify the processes and the factors that contribute to the implementation of IT governance. This study shows that the form of the IT governance framework ensuring success is related to achieving organizational goals, strategic alignment, resource management, and risk management in the Indonesian public sector, especially to the province of Gorontalo. The strategic role of IT governance can be an effective solution for making more consistent and transparent decisions about strategies and IT investments in public sectors.